Manajemen Risiko pada UKM Interior Menggunakan Kerangka Kerja ISO 31000: Studi Kasus Aviedz Aluminium - Umu Mahmudah; Ashilah Fauziyah; Siti Azmi Nur Islami; Yesica Maulidan; Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to identify, analyze, and evaluate potential business risks faced by Aviedz Aluminum, a micro, small, and medium enterprise (UMKM) operating in the interior and furniture sector, using the ISO 31000 risk management framework. The study employed a qualitative descriptive approach supported by a risk assessment using a 3x3 risk matrix and a SWOT analysis to identify internal and external factors impacting business sustainability. The study's findings revealed five main risk categories—market, financial, operational, human resources, and legal—with four events categorized as high-risk: price competition, rising raw material costs, supplier dependency, and limited skilled labor. The study concluded that a structured risk management framework helps UMKM anticipate uncertainty and strengthen their competitiveness through preventative and adaptive strategies.